2014
DOI: 10.1063/1.4900941
|View full text |Cite
|
Sign up to set email alerts
|

Modeling viscoelastic networks in Stokes flow

Abstract: Filamentous networks and elastic polymers immersed in a viscous fluid are central to many processes in biology. Here, we present a model of a discrete viscoelastic network coupled to a Stokesian fluid. The network is built out of a collection of cross-linked nodes where each link is modeled by one or more simple viscoelastic elements. The method of regularized Stokeslets is used to couple network dynamics with a highly viscous fluid in three dimensions. We use computational rheometry tests to characterize the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 44 publications
1
26
1
Order By: Relevance
“…In Wróbel et al (2014) we presented a model of a viscoelastic network coupled to a Stokesian fluid. These networks are constructed out of a collection of cross-linked nodes where each link is modelled by one or more simple viscoelastic elements.…”
Section: Viscoelastic Network Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…In Wróbel et al (2014) we presented a model of a viscoelastic network coupled to a Stokesian fluid. These networks are constructed out of a collection of cross-linked nodes where each link is modelled by one or more simple viscoelastic elements.…”
Section: Viscoelastic Network Modelmentioning
confidence: 99%
“…These networks are constructed out of a collection of cross-linked nodes where each link is modelled by one or more simple viscoelastic elements. Computational rheometry tests were used to characterize the viscoelastic structures (Wróbel et al 2014). It was found that when the linkages between nodes were modelled by Maxwell elements, the rheological behaviour of the system captured that…”
Section: Viscoelastic Network Modelmentioning
confidence: 99%
See 3 more Smart Citations